A Quantitative Framework for Assessing Public Investment in Tourism : An Application to Haiti - Banerjee, Onil (2015)
This study develops a linked regional computable general equilibrium and micro-simulation (RCGE-MS) model to assess the regional economy-wide and poverty impacts of a US$36 million investment in tourism in the south of Haiti. The first social accounting matrix for Haiti with a base year of 2012/2013 was constructed to calibrate the model. This research addresses three key gaps identified in the tourism impact assessment literature. First, a destination-specific tourism demand and value chain analysis was used to calibrate the shocks implemented in the model. Second, the RCGE-MS approach moves beyond the representative household configuration to enable more robust analysis of tourism investment impacts on poverty and income inequality. Third, results of this modelling were used to inform a social cost-benefit analysis to provide greater transparency in the evaluation of trade-offs between investment alternatives. Considering the investment and projected tourism demand, results show a positive impact on sectoral activity, especially for the hotel and restaurant sector (182.1% in 2040). The investment leads to a 2.0% increase in Gross Regional Product in 2040 compared with the baseline. The South Department’s exports are 4.7% below baseline in 2040 and imports are 6.1% higher due to the inflow of foreign exchange and the consequent appreciation of the regional real exchange rate, increased demand for most goods and services, and limited regional productive capacity. The rate of unemployment falls, beginning at 26% in 2013 and ending at 23.4% by 2040. The investment helps lift some of the poorest in the Haiti’s South out of poverty, reducing the poverty headcount by 1.6 percentage points. Driving this result is an increase in employment, the average wage and non-labor income. The linked RCGE-MS approach proves to be a powerful tool for assessing how tourism investments affect regional economic activity and revealing the mechanisms through which tourism can contribute to increase employment opportunities and reduce poverty.